2007
DOI: 10.1021/ja072194p
|View full text |Cite
|
Sign up to set email alerts
|

“Switching On” the Properties of Single-Molecule Magnetism in Triangular Manganese(III) Complexes

Abstract: The reaction between oxide-centered, triangular [MnIII3O(O2CR)6(py)3](ClO4) (R = Me (1), Et (2), Ph (3)) compounds and methyl 2-pyridyl ketone oxime (mpkoH) affords a new family of Mn/carboxylato/oximato complexes, [MnIII3O(O2CR)3(mpko)3](ClO4) [R = Me (4), Et (5), and Ph (6)]. As in 1-3, the cations of 4-6 contain an [MnIII3(mu3-O)]7+ triangular core, but with each Mn2 edge now bridged by an eta1:eta1:mu-RCO2- and an eta1:eta1:eta1:mu-mpko- group. The tridentate binding mode of the latter causes a buckling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
140
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(146 citation statements)
references
References 128 publications
6
140
0
Order By: Relevance
“…H, Me, Ph etc. ), are remarkable sources of homo-and heterometallic complexes with novel structures and interesting physical properties (Miyasaka et al, 2003;Stamatatos et al, 2007). A logical extension of such studies is the investigation of the coordination chemistry of analogous organic molecules in which the non-donor R group is replaced by a donor group such as pyridine, cyano etc.…”
Section: Chemical Contextmentioning
confidence: 99%
“…H, Me, Ph etc. ), are remarkable sources of homo-and heterometallic complexes with novel structures and interesting physical properties (Miyasaka et al, 2003;Stamatatos et al, 2007). A logical extension of such studies is the investigation of the coordination chemistry of analogous organic molecules in which the non-donor R group is replaced by a donor group such as pyridine, cyano etc.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Thus, angledependent EPR measurements were first performed so that the crystal could be aligned in situ (see [13] for details) for temperature and frequency-dependent measurements with the DC magnetic field applied approximately parallel to the average easy-axis direction, i.e., ~16° away from the local easy-axis (z-axis) of each molecule. As will be seen below, better sample alignment was achieved in the high-field magnet.…”
Section: Iii(b) High-frequency Epr Studiesmentioning
confidence: 99%
“…The triangular [Mn 3 -(μ 3 -oxo)] motif seen at the core of the molecule in Fig. 1 has been extensively studied in this regard [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. For a long time, it was believed that this topology would result exclusively in antiferromagnetic (AF) coupling and, hence, to a low-spin ground state.…”
Section: Introductionmentioning
confidence: 99%
“…To prepare hybrid materials, the comparison of conventional heating and microwave heating has shown that the crystalline quality and the yield of the product are obviously better with a shortened reaction time [63].…”
Section: Associated Technologiesmentioning
confidence: 99%